The Impact of Technology Use on Moral Decadence among Muslim Youth - Mokhtar, Marzni Mohamed; Lubis, Torkis; Ainin, Moh. (Khalifa Journal of Islamic Education, 2023)
The rapid development of digital technology has significantly influenced the lifestyle and behavior of young people, including in moral aspects. Online gaming, as one of the most popular forms of digital entertainment, is often associated with both positive and negative behavioral changes among adolescents. This study aims to examine how online gaming habits influence changes in adolescents’ morals and to identify possible solutions to these moral issues. This study employs a qualitative method with a phenomenological approach, using data obtained from in-depth interviews with twenty informants, including parents, school teachers, and community leaders. The informants were selected through purposive sampling. The interview data were analyzed using the Miles and Huberman analysis model. Overall, the findings reveal five negative impacts of online gaming habits on adolescents’ moral development: i) laziness, ii) disobedience to parents, iii) selfishness, iv) temperamental behavior, and v) dishonesty. The results of this study can serve as preliminary data for future research examining similar issues in different contexts and topics.